Tarbiyyah Aqliyyah (Study of Intellectual Intelligence Education in Hadith Perspective) - Kartika, Mitha; Alkhair, Muhammad Zia (Jurnal Riset Agama, 2023)
The purpose of this study is to determine intellectual quotient education from the perspective of hadith, in terms of hadith and its interpretation. This research is a type of qualitative research using the thematic hadith method (maudhu'i) with hadith interpretation approach. The results of this study have found seven hadiths in the books of Sahih Bukhari and Sahih Muslim about tarbiyyah aqliyyah, factors of influence, function, and the way to protect of intellectual quotient, also the learning concept of it. This study concludes that humans are given intellectual quotient potential by Allah with the purpose to always remember Allah, pay attention to creations, protect our self from bad things and increase knowledge in order to provide benefits on earth. Education becomes a medium in optimizing intellectual quotient, as education has been taught by Rasulullah Saw. in hadith that becomes a reference in intellectual quotient education.